Determinants and risk factors influencing stunting among toddlers - Muthara, Indah; Desmawati, Desmawati; Ali, Hirowati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Optimal growth and development in toddlers require appropriate food for growing toddlers. Stunting indicates inadequate nutritional intake in children. Purpose: To determine the risk factors and determinants associated with stunted infant development growth. Method: A descriptive quantitative with analytical survey specially focusing on cross-sectional method. The study took place from September 2024 to July 2025 in Dadok Tunggul Hitam Community Health Center, Padang. The independent variables studied were toddler age, gender, birth weight history, exclusive breastfeeding history, number of siblings, mother's age, mother's education, mother's occupation, family income, and gadget use, while the dependent variable was toddler growth. Using random sampling and the Slovin formula, 86 respondents meeting the inclusion and exclusion criteria were selected and categorized into two groups: suspect and normal. Data analysis began with univariate tests to describe the distribution of respondent characteristics, followed by bivariate analysis using the chi-square test and multivariate analysis with logistic regression. Results: The logistic regression results show that the most influential factor on the occurrence of suspicious developmental events is gadget use, especially in the high use category, with an increased risk of up to 18 times (Exp(B) = 18.125; p = 0.000). Toddler age also plays a significant role, with an approximately 5-fold increase in risk (Exp(B) = 5.406; p = 0.008). The number of siblings and family income also contribute each increasing the likelihood of developmental disorders by approximately 3–4 times (p < 0.05). Conclusion: Gadget use is the factor most strongly linked to growth delays in toddlers.